2001
DOI: 10.1046/j.1462-2920.2001.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

The probiotic potential against vibriosis of the indigenous microflora of rainbow trout

Abstract: The antibacterial properties of the indigenous microflora of rainbow trout (Oncorhynchus mykiss Walbaum) and the potential use of inhibitory bacteria as fish probiotics were investigated. A total of 1018 bacteria and yeasts were isolated on tryptone soy agar (TSA) from skin, gills and intestine. Forty-five of these inhibited growth of the fish pathogenic bacterium Vibrio anguillarum in a well diffusion assay. The antagonism was most prominent among Pseudomonas spp., as 28 (66%) of the antagonistic bacteria bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(113 citation statements)
references
References 50 publications
5
101
0
2
Order By: Relevance
“…1). This finding was in accordance with a previous study reported by Spanggaard et al (2001), which showed that a complete inhibition was discovered in V. anguillarum growth when co-cultured in TSB with five strains (E174, E156, AH2 and E102) of antagonistic Pseudomonas isolated from rainbow trout. Conversely, they also reported that two out of three respective Pseudomonas strains and Carnobacterium strains D4 and D5 were not able to inhibit target strains in M9GC broth and TSA diffusion assay, thus suggesting that substrate compositions significantly influenced the production of secondary metabolites.…”
Section: Discussionsupporting
confidence: 93%
“…1). This finding was in accordance with a previous study reported by Spanggaard et al (2001), which showed that a complete inhibition was discovered in V. anguillarum growth when co-cultured in TSB with five strains (E174, E156, AH2 and E102) of antagonistic Pseudomonas isolated from rainbow trout. Conversely, they also reported that two out of three respective Pseudomonas strains and Carnobacterium strains D4 and D5 were not able to inhibit target strains in M9GC broth and TSA diffusion assay, thus suggesting that substrate compositions significantly influenced the production of secondary metabolites.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Lactococcus lactis and Pseudomonas spp. can inhibit growth of Vibrio anguillarum (55,56). Because of the absence of an adaptive immune response during the larval-juvenile stages in zebrafish, incorporation of these bacterial species into the gut microbiota may be important for maintaining their health during this free-living period.…”
Section: Shared Characteristics Of the Zebrafish And Mammalian Digestivementioning
confidence: 99%
“…This definition is being constantly refined. Probiotics are associated with healthpromoting properties [320,321] and also with other benefits [322,323]. However, in aquaculture systems the interaction between the microbiota and the host is not limited to the intestinal tract, and given the nature of fish farming and the fact that water harbours microbial communities, a distinctive definition of probiotic for aquatic animals is accepted [324].…”
Section: Fish Skin Mucosal Immunologymentioning
confidence: 99%